Implementasi Penyusunan Anggaran Badan Layanan Umum dari Persepktif Good Governance (Studi di Fakultas Ekonomi dan Bisnis Universitas Brawijaya) - Munir, Saiful (Jurnal Ilmiah Administrasi Publik, 2016)
This study aimed to describe, analyze budget planning and to identify, analyze the supporting and obstacle factors of the Public Service Agency/ BLU pattern usage from good governance perspective. It used qualitative approach case study. The obstacle factors are incompetent human resource on IT, lacking knowledge on the budget cycle, unclear manual procedure, and short time budgetmaking. Supporting factors are Rector’s program, increase graduate and decrease undergraduate students number, leader motivation on budget planning, and convenient facilities.